An experimental study on vortex-rings colliding with surfaces with micro-features - Sanjay, Godsay Nikhil (Nanyang Technological University, 2023)
An experimental study is conducted and reported which investigates the effects of collision of vortex-rings with flat surfaces with protruding lattice posts using time- resolved particle-image velocimetry. A linear actuator and a piston-cylinder system was used to generate vortex-rings in a water tank using trapezoidal velocity profiles. Vortex-rings with Reynolds number of 2000 and 4000 were generated and were setup to collide with four flat plates with cylindrical lattice posts with varying post diameters and separation distances. Time-resolved particle-image velocimetry (TR-PIV) used to visualize the flow and obtain velocity and vorticity measurements show that a larger post diameter leads to faster transition to incoherence of the primary vortex ring. The effects of the separation distance were seen to follow an unusual trend where a reduction of the separation distance reduced the time taken for incoherence to set in except for the case with the lowest separation distance. This observation is attributed to the closely packed lattice posts exhibiting behaviours similar to that of a flat plate. An interesting vortex dipole was seen to form in the inner confines of the primary vortex ring upon collision in certain experiments due to boundary layer separation within the primary vortex ring rolling up into an internal secondary vortex core. The creation an ejection of secondary vortex structures outside of the primary vortex rings were only observed in experiments with a post diameter of 1mm and separation distances of 2.5mm and 10mm.